A STUDY TO ASSESS THE KNOWLEDGE, ATTITUDE, AND PRACTICE (KAP) REGARDING CHILDHOOD OBESITY AMONG MOTHERS RESIDING IN SELECTED RURAL AREAS - Menaga Gandhi. B,; Abirami. M, (The Bioscan, 2025)
Childhood obesity has emerged as a significant public health issue, necessitating effective strategies to foster awareness among mothers who play a crucial role in their children's dietary habits and lifestyle choices. Research underscores that understanding the knowledge, attitudes, and practices of mothers regarding childhood obesity is vital for developing preventive measures and interventions. Studies reveal that a substantial number of mothers possess inadequate knowledge about childhood obesity. For instance, a study conducted in Tamil Nadu, India, found that only 1% of the surveyed mothers had adequate knowledge about controlling childhood obesity, while the majority exhibited moderate understanding (Deepika et al., 2020). Similarly, in a study conducted in Tanzania, awareness about obesity and its implications was limited among parents, highlighting the need for targeted educational interventions (Muhihi et al., 2015). Proper knowledge about dietary practices, exercise, and obesity-related health risks is essential, as mothers often influence their children's eating behaviors and physical activities (Hudaib et al., 2024).